Are Household Surveys Like Tax Forms? Evidence from Income Underreporting of the Self-Employed - Hurst, Erik; Li, Geng; Pugsley, Benjamin (The Review of Economics and Statistics, 2014)
A large literature shows that the self-employed underreport their income to tax authorities. In this paper, we quantify the extent to which the self-employed also systematically underreport their income in U.S. household surveys. We use the Engel curve describing the relationship between income and expenditures of wage and salary workers to infer the actual income, and thus the reporting gap, of the self-employed based on their reported expenditures. On average, the self-employed underreport their income by about 25%. We show that failing to account for such income underreporting leads to biased conclusions in a variety of settings.